Endophyte Fungi to Control Helminthosporium turcicum, Fungi Causing Leaf Blight Disease - Ika Rochdjatun Sastrahidayat; Akhmat Riza Faizah; Anton Muhibuddin (KH. A. Wahab Hasbullah University, 2018)
Leaf blight disease is one of the most dangerous diseases of maize plant. This disease be able causing loss of maize harvest up to 40-70%. The cause of the leaf blight disease is Helminthosporium turcicum fungi. Biological control with endophytic fungi potentially used to control the pathogens as well as increase the resistance of plant induction to disease. Research was conducted in PT Bisi Inernational area, Tbk Farm Ngantang Malang Regency, Laboratory of Mycology Department of Plant Pest and Disease, Faculty of Agriculture Brawijaya University and Bioscience Laboratory Brawijaya University on December 2016 until July 2017. The exploration result of endophytic fungi of three varieties of maize were obtained 30 isolates, consisting of 14 non-pathogenic isolates and 16 pathogenic isolates. Based on the power inhibition percentage to the highest growth of H. turcicum is a fungi with NuII2, NuII4, PuIII3, DuIII3, NuII3 and PuIII1 isolates code. The most prevalent inhibition mechanism is pathogens and endophytic fungi competition. The 30 isolates identified were Colletotrichum sp, Fusarium sp, Curvularia sp, Acremonium sp dan Paecilomyces sp, meanwhile the other endophytic fungi is only found sterile hyphae thus difficult to identify up to the genus level. Keywords : Endophyte fungi, Zea mays, Helminthosporium turcicum